2017
DOI: 10.1002/ijop.12451
|View full text |Cite
|
Sign up to set email alerts
|

Person–city personality fit and entrepreneurial success: An explorative study in China

Abstract: While the study of personality differences is a traditional psychological approach in entrepreneurship research, economic research directs attention towards the entrepreneurial ecosystems in which entrepreneurial activity are embedded. We combine both approaches and quantify the interplay between the individual personality make-up of entrepreneurs and the local personality composition of ecosystems, with a special focus on person-city personality fit. Specifically, we analyse personality data from N = 26,405 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…An Australian study found that high congruence between participants' personalities and where they lived was linked to better mood (Murray et al, 2005 ). Similarly, person–city–fit had a positive effect on entrepreneurial success (Zhou et al, 2017 ) and self-esteem (Bleidorn et al, 2016 ). In a longitudinal study at the University of Berkeley, a better match between students and the university culture was correlated with higher levels of personality consistency and self-esteem as well as lower levels of Agreeableness and Neuroticism (Roberts and Robins, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Australian study found that high congruence between participants' personalities and where they lived was linked to better mood (Murray et al, 2005 ). Similarly, person–city–fit had a positive effect on entrepreneurial success (Zhou et al, 2017 ) and self-esteem (Bleidorn et al, 2016 ). In a longitudinal study at the University of Berkeley, a better match between students and the university culture was correlated with higher levels of personality consistency and self-esteem as well as lower levels of Agreeableness and Neuroticism (Roberts and Robins, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many different approaches to the measurement of fit have been employed (Phillips et al, 2010 ), ranging from intraclass correlation coefficients (ICC; Fulmer et al, 2010 ), sums of absolute differences (Noë et al, 2016 ), as well as sums of squared differences (Obschonka et al, 2013 ), and squared Euclidian distances (Musiol and Boehnke, 2013 ) to response surface analysis (RSA) techniques (Bleidorn et al, 2016 ; Denissen et al, 2017 ; Zhou et al, 2017 ). Undeniably, all of these methods have their merits.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect sizes were very small and only reliable for some personality traits (e.g., openness and agreeableness). Similarly, polynomial regressions have been used to examine effects of person-environment fit in traits on indicators of entrepreneurial success 30 , attachment 31 , as well as fit in values on anti-immigrant attitudes 32 and national pride 33 . These studies have demonstrated the utility of the polynomial method as a powerful tool for precisely estimating effects of person-environment fit.…”
mentioning
confidence: 99%
“…Success in running a company is of vital importance not only for entrepreneurs-business owners themselves but also for the society as a whole, since it leads to economic growth and job creation (e.g., van Praag and Versloot , 2007 ). Two kinds of indicators based on which businesses are judged to be successful have been considered in past research: financial indicators of firm performance (e.g., McGee et al, 1995 ; Murphy et al, 1996 ; Zhou et al, 2017 ) and indicators of entrepreneur’s satisfaction from running a firm (e.g., Gorgievski et al, 2011 ; Fodor and Pintea, 2017 ). Success evaluations were usually based on assessments made by entrepreneurs themselves ( Dijkhuizen et al, 2016 ; Przepiorka, 2016 ; Wach et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Popular opinion has it and many studies show ( Baron and Markman, 2003 ; Crane and Sohl, 2004 ; Steffens et al, 2009 ; Unger et al, 2009 ) that entrepreneurial success is evaluated from a financial perspective and identified with the financial yield of the company ( Steffens et al, 2009 ; Zhou et al, 2017 ). High financial outcomes and good position on the market are named as success indicators, together with other economic indicators of entrepreneurial success and firm performance ( van Praag and Versloot, 2007 ; Richard et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%